Determination of boundary effect on shear fracture energy at steel bar–concrete interface. (March 2016) - Yang, Shutong; Chen, Yujia; Du, Derun; Fan, Guoxi
Highlights: Correlation between pull-out load and interfacial fracture energy is established. We have obtained interfacial local shear fracture energy distribution analytically. Boundary effect on interfacial shear fracture energy is determined. Abstract: An analytical approach was proposed to predict the maximum pull-out load of steel bar from concrete, which is then related to the local fracture energy at the shear crack-tip region. Based on the comparisons between the analytically predicted and experimentally determined maximum pull-out loads under two extreme conditions, i.e., maximum crack-tip bridging with maximum fracture energy and zero crack-tip bridging with minimum fracture energy, the crack-tip local fracture energy indeed varies with the initial shear crack length. A tri-linear model was presented to well describe the local shear fracture energy distribution along the embedment length indicating the boundary effect.